HYPERSENSITIVITY PNEUMONITIS CAUSED BY INHALATION OF PARTICLES AT THE WORKPLACE - Elena Cojocaru; Gabriela Bordeianu; Cristian Cojocaru; Tudor Andrei Cernomaz; Loredana Liliana Hurjui (Romanian Society of Oral Rehabilitation, 2023)
Hypersensitivity pneumonitis is classified in the interstitial lung disease group, being caused by inhalation exposure to sensitized allergen. Exposure to inhalant allergens is often significant in the workplace, being favoured by the long duration of time spent at work, air circulation, and alveolar hyperventilation during high physical efforts and technological processes involved. Identifying the causative agents of Hypersensitivity pneumonitis is not always easy and symptoms often appear insidiously, after long periods of exposure, which can delay diagnosis. In addition, diagnostic tests do not always provide rapid positive results or involve invasive explorations that cannot be applied or are not accepted by patients. We exemplify these findings with a case study of Hypersensitivity pneumonitis following exposure to fish products and derivatives. Although initiation of treatment and cessation of exposure may improve symptoms and reverse pulmonary interstitial changes, exacerbations and rapid progression are not usual developmental pathways. Worker sensitization, effective ventilation of workplaces, wearing protective equipment (especially protective masks adapted to the type and size of particles released) and regular assessment of employees are the main measures to reduce the risk of most respiratory diseases.